(untitled) (The Review of Diabetic Studies, 2025)
This study examines the relationship between social support and the quality of life of paramedics working in the Saudi Red Crescent Authority. A sample of 200 paramedics was surveyed using a structured questionnaire consisting of two main axes: social support (7 items) and quality of life (8 items). Descriptive statistics showed that respondents reported moderate to high levels of social support, with family support scoring the highest, while communication channels within the organization received the lowest mean score. Regarding quality of life, physical health was rated the highest, while time for recreational activities was rated the lowest, indicating challenges in achieving work–life balance. The reliability analysis confirmed strong internal consistency for both scales (Cronbach’s Alpha = 0.86 for social support, 0.88 for quality of life). Pearson correlation analysis revealed a significant positive relationship between social support and quality of life (r = 0.62, p < 0.01). Linear regression analysis further demonstrated that social support is a significant predictor of quality of life, explaining 38% of its variance (R² = 0.38). Exploratory Factor Analysis supported the two-dimensional structure of the instrument, with items loading clearly on their respective factors. These findings highlight the pivotal role of social support in enhancing the quality of life among paramedics, who often face stressful and demanding work conditions. The results emphasize the importance of strengthening institutional support mechanisms, improving organizational communication, and ensuring opportunities for work–life balance to sustain both the well-being of paramedics and the efficiency of emergency healthcare services.